2023
DOI: 10.1038/s41467-023-36575-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of lysophosphatidylserine receptor GPR174 ligand recognition and activation

Abstract: Lysophosphatidylserine (LysoPS) is a lipid mediator that induces multiple cellular responses through binding to GPR174. Here, we present the cryo-electron microscopy (cryo-EM) structure of LysoPS-bound human GPR174 in complex with Gs protein. The structure reveals a ligand recognition mode, including the negatively charged head group of LysoPS forms extensive polar interactions with surrounding key residues of the ligand binding pocket, and the L-serine moiety buries deeply into a positive charged cavity in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Yet, to the best of our knowledge, no such small molecule modulators (antagonists) to GPR174 have been reported. However, very recently, a few reports describe the three-dimensional structures of human GPR174 bound to lyso-PS in complex with the Gα s G-protein that were solved using cryoelectron microscopy. ,, These structures of the ternary complex provide new insights into the selective ligand (lyso-PS) recognition by GPR174 and activation of this receptor upon lyso-PS binding and coupling to the Gα s G-protein ,, and should now pave the way for developing antagonists to GPR174.…”
Section: Lyso-ps Receptorsmentioning
confidence: 99%
“…Yet, to the best of our knowledge, no such small molecule modulators (antagonists) to GPR174 have been reported. However, very recently, a few reports describe the three-dimensional structures of human GPR174 bound to lyso-PS in complex with the Gα s G-protein that were solved using cryoelectron microscopy. ,, These structures of the ternary complex provide new insights into the selective ligand (lyso-PS) recognition by GPR174 and activation of this receptor upon lyso-PS binding and coupling to the Gα s G-protein ,, and should now pave the way for developing antagonists to GPR174.…”
Section: Lyso-ps Receptorsmentioning
confidence: 99%
“…However, we could not detect any activation of LPS 3 by a CCL21 recombinant protein in both the TGFα shedding assay and the NanoBit Gα dissociation assay, although LysoPS activated LPS 3 in both assays (Figure 5). Very recently, Liang et al revealed the structural basis for the recognition of LysoPS and also Gα s protein by LPS 3 55 . Considering that the ablation of CCR7, which is a classical receptor for CCL21, markedly reduced the CCL21‐induced LPS 3 ‐Gα i coupling and downstream migration, it requires further structural support to define whether CCL21 is a direct ligand for LPS 3 .…”
Section: Roles Of Lysops Signaling In Immune Modulationmentioning
confidence: 99%
“…Very recently, Liang et al revealed the structural basis for the recognition of LysoPS and also Gα s protein by LPS 3 . 55 Considering that the ablation of CCR7, which is a classical receptor for CCL21, markedly reduced the CCL21-induced LPS 3 -Gα i coupling and downstream migration, it requires further structural support to define whether CCL21 is a direct ligand for LPS 3 . A single injection of TNP-conjugated ovalbumin (TNP-OVA) with an alum adjuvant into the footpads of a mouse triggers a series of basic immune responses within a week, 52 including antigen presentation to T and B cells, activation, differentiation, and expansion of T and B cells (Figure 6A).…”
Section: Gpr174/lpsmentioning
confidence: 99%
“…GPR174 also features an extended binding pocket that traverses the lipid bilayer; however, there are distinct differences in the extracellular region, including in the placement of ECL2 (Figure 4D). 16 Additionally, GPR174 has a pronounced kink in TM5, which results in differential placement of the lipid in its binding pocket.…”
mentioning
confidence: 99%
“…Moreover, ECL2 also adopts a conformation different from that in GPR3, and GPR119 engages with the lipid tail via a distinct series of amino acids within the hydrophobic channel (Figure S8). GPR174 also features an extended binding pocket that traverses the lipid bilayer; however, there are distinct differences in the extracellular region, including in the placement of ECL2 (Figure D) . Additionally, GPR174 has a pronounced kink in TM5, which results in differential placement of the lipid in its binding pocket.…”
mentioning
confidence: 99%